Acute aortic dissection: pathogenesis, risk factors and diagnosis (Swiss Medical Weekly, 2017)
Acute aortic dissection is a rare but life-threatening condition with a lethality rate of 1 to 2% per hour after onset of symptoms in untreated patients. Therefore, its prompt and proper diagnosis is vital to increase a patient’s chance of survival and to prevent grievous complications. Typical symptoms of acute aortic dissection include severe chest pain, hypotension or syncope and, hence, mimic acute myocardial infarction or pulmonary embolism. Advanced age, male gender, long-term history of arterial hypertension and the presence of aortic aneurysm confer the greatest population attributable risk. However, patients with genetic connective tissue disorders such as Marfan, Loeys Dietz or Ehlers Danlos syndrome, and patients with bicuspid aortic valves are at the increased risk of aortic dissection at a much younger age. Imaging provides a robust foundation for diagnosing acute aortic dissection, as well as for monitoring of patients at increased risk of aortic disease. As yet, easily accessible blood tests play only a small role but have the potential to make diagnosis and monitoring of patients simpler and more cost-effective.